Prevalence and Significance of Abnormal Tactile Responses in Young Children with Autism - Silva, MD, MPH, Louisa MT.; Schalock, BSc, Mark (North American Journal of Medicine and Science, 2013)
With the inclusion of sensory abnormalities in the DSM-V criteria for autism, the multifocal touch/pain abnormalities reported in young children with autism are no longer comorbid symptoms, and it has become an urgent priority to identify their nature and significance. A recent study differentiated children with autism from typical and otherwise developmentally delayed groups on the two-fold basis of mixed allodynia and hypoesthesia, and severe global self-regulatory delay. In this study, we retrospectively analyzed case records for 266 pre-school children with autism and typical development to verify recent findings, assess the prevalence and location of tactile abnormalities in the autism group, and explore the relationship between tactile abnormalities and self-regulatory delay. Results differentiated the autism group by severity of tactile abnormality [F(1,262) = 172.8, p < .001] and self-regulatory delay [F(1,262) = 232.8, p < .001]. Allodynia was reported in 100% of the autism group by parent report and 98% by therapist report; hypoesthesia was present in 65% by parent report. Tactile abnormalities were directly, linearly related to self-regulatory delay (r = .727, p < .001) in both groups. The sense of touch has not been fully evaluated in autism, and there is insufficient quantitative evidence to conclude that it is intact. Mixed allodynia and hypoesthesia are typical signs of sensory neuropathy. Evidence of their near universal presence in young children with autism, and direct relationship to self-regulatory delay underscores the urgent need to fully evaluate the sense of touch in autism and rule out sensory neuropathy. [N A J Med Sci. 2013;6(3):121-127. DOI: 10.7156/najms.2013.0603121]